Pengaruh Lama Fermentasi Terhadap Karakteristik Minuman Probiotik Sari Buah Sirsak (Annona muricata Linn) - Agus Widyantara, I Wayan; Ayu Nocianitri, Komang; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p05, 2020)
This research aims to identify the effect of fermentation time on the characteristics of soursop juice (Annona muricata Linn) probiotic drink as well as to determine the specific fermentation time that produces good characteristics of soursop juice probiotic drink. This study used a randomized block design (RBD) of one treatment factor with different periods of fermentation time that consist of 18 hours, 20 hours, 22 hours, 24 hours, and 26 hours. The treatment was repeated 3 times to obtain 15 experimental units. The data was analyzed with analysis of variance (ANOVA) and if the treatment had a significant effect, then followed by the Duncan test. The results showed that the length of fermentation in soursop juice probiotic drink did not significantly affect the total LAB, total sugar, total acid, pH, and sensory tests. Fermentation time of 18 hours resulted the best characteristics of soursop juice probiotic drinks with an average total value of BAL 10,87 Log CFU / ml, total sugar 10,61%, total acid 1,37%, total sugar, pH 3,92, colour, aroma, and taste rather liked with rather acidic and rather sweet criteria and overall acceptance is rather liked. Keywords: fermentation time, soursop juice, probiotics.